Task-based language teaching intervention to improve english speaking performance: A case study of secondary school students in Mardan, Pakistan - Hayat Ullah; Rose Patsy Tibok; Wong, Jane Kon Ling (Centre for research on poverty and attitude, 2023)
This study explores the significance of English proficiency in Pakistan, focusing on District Mardan and the challenges students face in speaking English fluently due to ineffective teaching methods. The study investigates the potential benefits of Task-Based Language Teaching (TBLT) in improving English speaking skills among secondary school students. The research aims to understand the perspectives of English as a Second Language (ESL) teachers regarding integrating TBLT into the existing English Language Teaching (ELT) framework. English language teachers from government schools were the participants in the study. The data collection method consists of questionnaires for English teachers. Thematic analyses were employed to analyze qualitative data, ensuring a comprehensive investigation of English language teaching in government secondary schools focusing on TBLT as a teaching methodology. Many of the teachers were in favor of TBLT. The study's results revealed TBLT as an effective method of improving English language speaking skills at the secondary school level. Findings show that the education department should promote task-based teaching methodologies in public and private section institutions.